2x + 3=7x
7x-1=2x+5 7x-2x=5+1 5x=6 x=6/5=1.2
It equals 53X- a number is squared when it is multiplied by itself, so 7X by 7X = 49X. 2X by 2X =4X, so 49X + 4X is 53X.
7x + 7 + 6x - 9 = 13x - 2
2x + 5x = 35 7x = 35 x = 35/7 x = 5
7x-5+2x=3-4x+12 7x+2x-5=3+12-4x 9x-5=15-4x 9x+4x-5=15-4x+4x 13x-5=15 13x-5+5=15+5 13x=20 13x/13=20/13 x=20/13
It is 9x
2x + ? = 9x9x - 2x = 7xso...2x + 7x = 9x
13x = -156 so x = -12
2x+7x-10=4x+3-2x 9x-10=2x+3 7x=13 x=13/7ans
-2x + 8 = 7x - 10 is technically an equation, in and of itself.
It is an equation and the value of x is 1
2x+3 = 9x 3 = 9x-2x = 7x 7x = 3 x = 3/7
The value of x is 1
X = -3